The missing number is 3.
So, Beejal adds 3 to both sides of the equation, resulting in:
y^7 = 39 + 3
y^7 = 42
After that, Beejal multiplies both sides of the equation by 1/7, resulting in:
(1/7)y^7 = (1/7)42
y^7/7 = 6
Therefore, Beejal's first step is adding 3 to both sides of the equation and his second step is multiplying by 1/7 on each side.
Beejal is solving the equation y7 − 3 = 39.(1 point)
As a first step, he starts by adding
to both sides of the equation, and then continues by multiplying by
on each side.
2 answers
here are all the answers:
1: 1
2: 45
3: 8
4: 9
5: 3 and 7
1: 1
2: 45
3: 8
4: 9
5: 3 and 7